The Healthy Card as Early Detection of Stunting and Children’s Nutrition Status on Kindergarten Student - Casman; Ita Pursitasari; Medya Aprilia Astuti; Mutia Farlina; Tri Setyaningsih (MITRA: Jurnal Pemberdayaan Masyarakat, 2023)
Stunting is a worldwide issue that affects children, in which Indonesia has a high stunting rate of 36.4 percent of children stunted. Stunting has a significant negative impact on children's growth and development including nutritional status. To avoid this, it is vital to discover the problem as soon as feasible. The Card to Health (Kartu Menuju Sehat/KMS) and the Denver II instrument can be used for early detection, as well as child growth and development examinations. However, kindergarten teachers, who are on the front lines of education, do not yet have access to KMS and Denver II. The purpose of this activity is to increase teachers' abilities to diagnose stunting in children at a young age using KMS and Denver II. During the months of August to November 2019, the Pelangi Islamic Kindergarten in Depok carried out community service activities. Thirteen teachers and 18 pupils took part in the activity. As a result, 100 percent of teachers improved their ability to use KMS, and up to three children were classified as fat, one had autism, and one had reservations about Denver II. At the Pelangi Islamic Kindergarten, no students are considered stunted. Stunting and nutritional status can be detected by community service activities, and teachers' capacity to detect stunting and nutritional status using KMS and Denver II can be improved significantly.